2004
DOI: 10.1046/j.1601-183x.2003.0046.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between Drosophila flies in searching behavior

Abstract: In Drosophila melanogaster food search behaviour, groups of flies swarm around and aggregate on patches of food. We wondered whether flies explore their environment in a cooperative way as interactions between individual flies within a population might influence the flies' ability to locate food sources. We have shown that the food search behavior in the fruit fly Drosophila is a two-step process. Firstly, 'primer' flies search the environment and randomly land on different food patches. Secondly, the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 50 publications
3
63
0
Order By: Relevance
“…For example, it has been shown that social interactions may be related to cooperative behavior when searching for food (Tinette et al, 2004) and in larval burrowing behavior (Wu et al, 2003), and may influence circadian timing (Levine et al, 2002) and even life-span determination (Ruan & Wu, 2008).…”
Section: Social Behaviormentioning
confidence: 99%
“…For example, it has been shown that social interactions may be related to cooperative behavior when searching for food (Tinette et al, 2004) and in larval burrowing behavior (Wu et al, 2003), and may influence circadian timing (Levine et al, 2002) and even life-span determination (Ruan & Wu, 2008).…”
Section: Social Behaviormentioning
confidence: 99%
“…This novel approach raises the question of whether flies, just like ants, can collectively decide to exploit selected resources in their environment. Previous studies in D. melanogaster have involved situations in which flies were observed aggregating in uniform environments, such as a large food patch , or choosing one of several food patches of differing qualities (Bartelt et al, 1985;Durisko and Dukas, 2013;Tinette et al, 2004). Although these observations constitute an important first step, a comprehensive assessment of the mechanisms driving collective foraging decisions requires disentangling the attractive power of food itself from that of conspecifics, or their potential interactive effects.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous observation in the fruit fly, D. melanogaster in which the food-searching behavior in fruit flies comprised two steps. Firstly, the primer fly searched the environment and randomly landed on different food patches, and secondly, the remaining group of flies moved to the most favorable food source and aggregated there (Tinette et al 2004). The social interactions between flies appeared to affect their choice of a specific food patch.…”
Section: Discussionmentioning
confidence: 99%